Physical activity of pregnant women - Korabiusz, Katarzyna; Wawryków, Agata; Fabian-Danielewska, Anna; Stecko, Monika; Żukowska, Magdalena; Janik, Inga; Andrusewicz, Wojciech; Torbe, Andrzej (Journal of Education, Health and Sport, 2018)
Every pregnant woman should be aware that her every day health habits affect the child’s health, but also her health during pregnancy, delivery and post-partum period. Physical activity plays an important role during pregnancy. It improves the overall physical condition and prevents many ailments of pregnancy. The most important aspect of taking physical activity during pregnancy is the right choice of exercise and regularity and appropriate technique. Due to many benefits of proper exercises during pregnancy, pregnant women should be encouraged and educated in this area.